Synthesis, Biological Evaluation, and Molecular Modeling Studies of New Thiadiazole Derivatives as Potent P2X7 Receptor Inhibitors - Gonzaga, Daniel T. G.; Oliveira, Felipe H.; Ranke, N. L. von; Pinho, G. Q.; Salles, Juliana P.; Bello, Murilo L.; Rodrigues, Carlos R.; Castro, Helena C.; Souza, Hellen V. C. M. de; Reis, Caroline R. C.; Leme, Rennan P. P.; Mafra, João C. M.; et al. (Frontiers in Chemistry, 2019)
Thiadiazole analogs synthesis has used azole as the core skeleton to develop P2X7 receptor (P2X7R) inhibitors. Pyrazole and 1,3,4-thiadiazole cores junction formed twenty new lead compound. P2X7R inhibition in vitro was evaluated in mice peritoneal macrophages, HEK-293 transfected with hP2X7R (EtBr uptake assay) and THP-1 cells (IL-1β ELISA assay). The thiadiazole derivatives 9b, 9c, 9f, and 11c, showed potent inhibitory effects with IC50 values ranging from 16 to 122 nM to reduced P2X7R-mediated dye uptake and 20 to 300 nM to IL-1β release. Besides, the in vitro absorption, distribution, metabolism, excretion, and toxicity (ADMET) profile of the four more potent derivatives were determined to be in acceptable ranges concerning metabolic stability and cytotoxicity. Molecular docking and molecular dynamics simulations studies of the molecular complexes human P2X7R/9f and murine P2X7R/9f indicated the putative intermolecular interactions. The compound 9f showed affinity mainly to Arg268, Lys377 and Asn266 residues. These results suggest that thiadiazole derivatives may be promising novel P2X7R inhibitors for the development of anti-inflammatory drugs.